2006
DOI: 10.1088/0960-1317/16/5/028
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of adaptive microbolometers

Abstract: We report the first practical results on design and characterization of adaptive microbolometers with a thermally tuned responsivity. Such devices are needed to simultaneously image scenes that contain objects at ambient and extremely hot temperatures. In the high detectivity state, the microbolometers are operated similar to standard commercial devices. In the low detectivity state, portions of the support beams are brought in contact with the substrate, which thermally shorts the devices on a pixel-by-pixel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…On account of these characteristics, they are indispensable in sensing, actuation, and switching in micro/nano-devices. [1][2][3][4][5][6][7][8][9] While a few devices can be fabricated using wafer-level direct bonding, 4 most suspended films in such devices are fabricated by film deposition followed by etching of the sacrificial layers. Such fabrication is known to generate "fabrication stiction" problems, where thin films are pinned to substrates during aqueous rinse and dry cycles.…”
mentioning
confidence: 99%
“…On account of these characteristics, they are indispensable in sensing, actuation, and switching in micro/nano-devices. [1][2][3][4][5][6][7][8][9] While a few devices can be fabricated using wafer-level direct bonding, 4 most suspended films in such devices are fabricated by film deposition followed by etching of the sacrificial layers. Such fabrication is known to generate "fabrication stiction" problems, where thin films are pinned to substrates during aqueous rinse and dry cycles.…”
mentioning
confidence: 99%
“…From these two figures, it can be observed that the thermal conductance is overestimated when using Eq. (5) and when the proposed model does not take into consideration the constriction resistance. On the other hand, as it was mentioned in Section 3.2, when the model includes the constriction resistance, the thermal conductance is underestimated due to the 2D channel approximation.…”
Section: Nomentioning
confidence: 99%
“…Therefore, careful consideration of the thermal conductance parameter is required at the design stage to optimize sensitivity without compromising speed. Current methods to estimate the thermal conductance in microbolometers only consider the temperature drop within the arms themselves [3][4][5]. However, as will be demonstrated later, the thermal conductance parameter depends on the plate dimensions as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although VO x microbolometers are mostly used as detectors under vacuum conditions to achieve high sensitivity, drawbacks exist when capturing scenes with high thermal dynamic range or high temperature regions like explosions, fire, fuselage and the sun [14,15]. The output of these sensors saturate and take a long time to recover.…”
Section: Introductionmentioning
confidence: 99%